2019
DOI: 10.1016/j.puhe.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

What the public think about participation in medical research during an influenza pandemic: an international cross-sectional survey

Abstract: What the public think about participation in medical research during an influenza pandemican international cross-sectional survey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…Interestingly, participants felt safe to come‐in for their appointments despite endorsing high levels of panic the general public had about the pandemic. Although these results of willingness to participate are in keeping other research studies conducted during pandemics, they could change vastly as the COVID‐19 pandemic peaks …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, participants felt safe to come‐in for their appointments despite endorsing high levels of panic the general public had about the pandemic. Although these results of willingness to participate are in keeping other research studies conducted during pandemics, they could change vastly as the COVID‐19 pandemic peaks …”
Section: Discussionmentioning
confidence: 98%
“…Hence, it is important to learn the factors that shape oneʼs willingness to participate in clinical research particularly during a pandemic. The general public is supportive of clinical research in general, and even during pandemics . Gobat et al (N = 6,804) reported that 82% of the participants considered that it was important to conduct medical research during epidemics .…”
mentioning
confidence: 99%
“…Patients agree with this approach, as shown by a number of studies conducted before the current pandemic. 7,8 Canada's clinical research infrastructure is being scaled quickly to meet these scientific and ethical imperatives, similar to trials that were conducted during the Ebola epidemic. 9 The Canadian Institutes of Health Research and its partners launched a rapid research funding opportunity on COVID-19 in February 2020, completing applications, submissions, peer review and initial funding decisions within 18 days.…”
Section: Generating Randomized Trial Evidence To Optimize Treatment Imentioning
confidence: 99%
“…This strategy allows clinicians to be satisfied that they are doing everything possible for their severely ill patients while contributing to new knowledgean approach with which patients also agree. 35 We must avoid the 'just do it' option of administering therapies based on unreliable observational evidence and instead commit to reducing uncertainty by testing therapies in RCT as the 'must learn' alternative. It is not a matter of choosing between one or the other.…”
Section: Box 2 Rapidly Cycling Trial Designsmentioning
confidence: 99%